Effect of Heavy Metals Emissions on Ecosystem of Pakistan - Muhammad Asif; Bushra Sharf; Saqaina Anwar (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
Environmental contamination is one of the significant problems of modern society. Heavy metal pollutants include zinc, arsenic, nickel, cadmium, copper, lead, chromium, manganese, and iron etc. Their universal bioavailability accumulation in the food chain causes severe effects on human health. The lives of living species will be preserved by unique heavy metal treatments to improve the air, soil, and water quality. This review article represents a glimpse of heavy metal contamination in several areas of Pakistan over the past few years, that assess the heavy metal especially the contamination in water (groundwater, surface water, and wastewater), soil, and particulate matter. The listed pollution affects the quality of drinking water, the ecological environment, and the food chain. The toxicity induced by contaminated water, soil, and air causes a genuine threat to human health. Moreover, the technologies to overcome this problem have also been reported in it.